Prosumers in the wine market: An explorative study - Marc Dressler (Wine Economics and Policy, 2016)
Winning business models increasingly build on stronger integration of clients in the world of production. Empirical evidence on such prosuming for the wine industry is lacking. A multidimensional approach and 321 interviews with wine consumers allowed to explore presuming interest with descriptive, correlation, and a two-step cluster analyses. The study results support the relevance of customer integration in the world of wine. Two clusters divide the wine consumers: prosuming interested versus prosuming reluctant consumers. Against literature based expectations, demographics or wine knowledge are less cluster determinant. Challenging wine consumer groups, especially the younger generation, can be attracted via prosuming. New client relationships can be built with loyalty and price premium opportunities in a market where these two success variables are under pressure. Despite a general openness and curiosity from the client side the interviews revealed no enthusiasm for prosuming and disclosed a segment of clients with low and limited involvement interest. Hence careful resource allocation is recommended. Prosuming needs managerial attention and a strategic approach adapting the business model to integrate interested clients.
Keywords: 330; Co-creation; Involvement; Prosuming; Strategy